PERLINDUNGAN HUKUM TERHADAP DOKTER YANG TELAH MELAKSANAKAN TUGASNYA SESUAI DENGAN PROSEDUR MENURUT UNDANG-UNDANG NOMOR 29 TAHUN 2004 TENTANG PRAKTIK KEDOKTERAN - Haeruddin Fajar (Journal of Law ( Jurnal Ilmu Hukum ), 2019)
Abstract             Doctors are scientists who have been professionally educated to provide help and medical service to people in need. Sometimes a doctor has performed his actions following standard operating procedures, but in the final result, there are undesirable both patients’ families, the number of cases against doctors who are suspected of making mistakes or more often we hear in other words malpractice.            This type of research used in this research is normative legal research, namely research that studies document studies, namely various secondary data such as regulations, judicial decisions, legal theories, and scholars’ opinions.            The result of this study is that in carrying out their duties doctors obtain legal protection as long as it is by procedures. The form of legal protection is contained in the book Philips M. Handjon, it was explained that there are two forms of legal protection, the first is the protection of preventive law. Preventive law, namely the people, can express their opinions before the government decision gets a definitive form that aims to prevent disputes. And the legal consequences received by the doctor if found guilty in carrying out medical actions resulting in the death of the patient contained in law number 23 of 1992 concerning health article 82 paragraph 1 letter (a) states “who without expertise or authority intentionally performs treatment and or the treatment referred to in article 32 paragraph (4) shall be sentenced to a maximum of 5 years imprisonment or a maximum fine of one hundred million rupiahs. Violations of the article are threatened with criminal penalties if the patient dies then the sentence is added by one-third. Keywords: doctor, legal protection, legal consequences.